Peningkatan Literasi Kesehatan tentang Gout Artritis pada Lansia - Awal Tunis Yantoro; Dea Ananda; Desi Fayra Azizah; Diana Fatimah; Doni Hidayat; Eka Nurlaela; Dwi Novitasari (Yayasan Inspirasi El Burhani, 2026)
Introduction: Gout is a disease that causes pain in the joints caused by the buildup of uric acid crystals. Objective: The purpose of this community service was to improve the understanding of the elderly at the Community Health Service Mugi Sehat Dukuhwaluh. This community service aims to explore and evaluate the impact of gout interventions on the elderly. Method: The way to overcome gout problems in the elderly is to conduct mass counseling for the elderly at Community Health Service Dukuhwaluh with a total of 22 participants. By using the method of presentation, discussion and working on pre test and post test questions with powerpoint slide media and leaflets about gout. Results: The results were that the elderly aged 35-59 years had a frequency of 8 and a percentage of 38%, the elderly aged 60-77 years had a frequency of 13 and the percentage was 62%. The level of knowledge of the elderly pre-test is both 6 and the percentage is 30%, while the pre-test is medium frequency 15 and the percentage is 70%, the level of knowledge in the post test is both 21 and the percentage is 100% while the medium post test has a frequency of 0 and the percentage is 0%. The number of participants who did not have a history of gout arthritis was 14 (66.7) more than those who had a history of gout arthritis 7 (33.3). Conclusion: education of gout arthritis is well organized. Increasing level of understanding of the elderly about gout arthritis.